The ability of orthodontists and oral/maxillofacial surgeons to predict eruption of lower third molar - Aline do Carmo Bastos; Joelma Bezerra de Oliveira; Karina Flexa Ribeiro Mello; Patrícia Botelho Leão; Flavia Artese; David Normando (SpringerOpen, 2016)
Abstract Background The aim of this study was to evaluate the ability of oral/maxillofacial surgeons (OMFSs) and orthodontists to predict third molar eruption by examining a simple panoramic radiograph in cases where full spontaneous eruption occurred. Methods Panoramic radiographs of 17 patients, 13-16 years of age, were obtained just after orthodontic treatment (T1), when the third molars were intraosseous. The radiographs at T1 were presented to 28 OMFSs and 28 orthodontists-who were asked to give a prognosis for the lower third molars on both sides (n = 34). The full spontaneous eruption of all third molars was clinically observed when patients were older than 18 years (T2). These teeth were clinically asymptomatic at T1 and T2. Results OMFSs decided by extractions in 49.6 % of cases while orthodontists in 37.8 % (p < 0.001), when the radiographs were examined at T1. Agreement between OMFSs and orthodontists was excellent (Kappa = 0.76, p < 0.0001), as well as intragroup agreement for both OMFSs (Kappa = 0.83) and orthodontists (Kappa = 0.96). Conclusions Despite a remarkable agreement for third molar prognosis, orthodontists and OMFSs were unable to predict lower third molar eruption by examining a simple panoramic radiograph. Both indicated extractions of a considerable number of spontaneously erupted asymptomatic teeth.